A novel atmospheric pressure hydrolysis without stirring and combustion–calcination process for the fabrication of magnetic Fe3O4/α-Fe2O3 heterostructure nanorods. (1st July 2022) - Qin, Jiang; Liu, Min; Wang, Zhou; Pei, Lin; Zhao, Mingjie; Zhou, Qunmei; Bin Wu,; Liu, Ruijiang
Abstract: Atmospheric pressure hydrolysis without stirring and a combustion–calcination method were utilized to fabricate magnetic Fe3 O4 / α -Fe2 O3 heterogeneous nanorods. First, the β -FeOOH nanorods were fabricated via hydrolysis, and the concentration of Fe 3+, hydrolysis temperature, and hydrolysis time were optimized. The optimal fabrication conditions were as follows: a 0.1 M FeCl3 solution was hydrolyzed at 90 °C for 2 h. The average length and diameter of the β -FeOOH nanorods fabricated under the optimal conditions were approximately 216 and 58 nm, respectively. Subsequently, Fe3 O4 / α -Fe2 O3 heterogeneous nanorods were fabricated via a combustion–calcination process. The volume of absolute ethanol, calcination temperature, and calcination time were investigated to optimize the fabrication conditions of Fe3 O4 / α -Fe2 O3 heterogeneous nanorods under the following conditions: absolute ethanol: 50 ml; calcination temperature: 300 °C; and calcination time: 2 h. Magnetic Fe3 O4 / α -Fe2 O3 heterogeneous nanorods fabricated under optimal conditions were characterized with an average length of 199 nm, an average diameter of 51 nm, a zeta potential of +17.2 mV, and a saturation magnetization of 13 emu·g –1 .